Perceived Socio-Cultural Factors Affecting the Re-integration of Discharged Prisoners: A Case Study of Ilorin Emirate - Salihu, Habeeb Abdulrauf (NIU Journal of Social Sciences; Vol 4 No 2 (2018): KIU Journal of Social Sciences, Vol. 4 No. 2, June 2018, 2018)
This study examines the perceived socio-cultural factors affecting the re-integration of the discharged prisoners in Ilorin Emirate of Kwara State, Nigeria. Questionnaire and interview were the instruments of data collection. Simple random and purposive sampling techniques were adopted to select a total of 1187 and 3 (1190) respondents respectively. The data was analysed using Statistical Package for Social Scientists and thematic analysis. The study found that there is a relationship between the socio-cultural factors and reintegration challenges of discharged prisoners in Ilorin. The study concludes that a successful reintegration is pertinent to society’s readiness to receive and accept the discharged prisoners. Thus, the paper suggested that a coordinated effort to develop public enlightenment programs aimed at sensitising individuals and communities (at both micro and macro level) about the responsibilities of the society and significant roles members could play in the reintegration process of discharged prisoners would seem appropriate. Keywords: Socio-cultural; Discharged-prisoners; Prison; Ex-convict; Reintegration; Ilorin; Nigeria